Analysis of the Application of Service Innovation to the Study of Public Service Quality in the "House of the Sky" in Sidenreng Rappang Regency - Aris Baharuddin; Asmar Asmar; Asmilah Abdullah (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
Service innovation is adopted not only as a measure to deal with changes in the organizational environment. More than that, the purpose of service innovation is to improve the quality of public services. Public service innovation continues to be carried out by the government in various sectors, one of which is in the education sector. The education sector is a sector that has an important role that can make a major contribution to national development. Quality education actually gives birth to superior resources in carrying out nation building. This study aims to find out how the application of the "Rumah Langit" service innovation affects the quality of public services felt by the people of Sindenreng Rappang Regency. This research will be conducted from May to November 2023. The research locations include four villages in Sidenreng Rappang Regency. The research method to be used is to use quantitative methods with the research population, namely the people of Sidenreng Rappang Regency who are recipients of the "Rumah Langit" service innovation. This research sample was taken using simple random sampling technique. The tests used in this research are validity tests, reliability tests, descriptive statistical analysis and inferential statistical analysis. The research results show that the indicators used for each variable are in the good category. Through the results of the significance test, it shows that service innovation has a significant effect, where the significant value is smaller than the alpha value, while the calculated t value is greater than the t table, so it can be concluded that there is a significant influence between service innovation on the quality of public services in the "Rumah Langit" service in Sidenreng Rappang Regency.